Crisis communications management - Wheeler, Adrian (PRCA practice guides, 2018)
Can you control a crisis? No but with adequate preparation you can control the reputational consequences. Reputational damage is rarely caused by the crisis itself but, instead, by what the organisation does and says under the media spotlight.This PRCA Practice Guide describes how to invest in readiness and what to do when a crisis strikes. Coverage includes contingency planning, stakeholder identification, crisis communications policy, spokesperson training, the 'Red Book', dark sites, rehearsals and simulations, locations and resources, taking the initiative, and managing the aftermath. The book also covers in detail the role of the mainstream and online media, recommending steps to neutralise hostility and shut down ill-informed comment.Including numerous real-life examples, discussion topics and advice from PR experts, journalists and editors, Crisis Communications Management is intended as an essential guide for public relations professionals, and the people who work with them during a crisis, on how to navigate the turmoil and emerge from a crisis with reputation and credibility intact.